2003
DOI: 10.1128/aac.47.7.2354-2357.2003
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial Susceptibility of Brachyspira pilosicoli Isolates from Humans

Abstract: The in vitro antimicrobial susceptibility of the anaerobic intestinal spirochete Brachyspira pilosicoli was investigated by an agar dilution method. Human (n ‫؍‬ 123) and porcine (n ‫؍‬ 16) isolates were susceptible to metronidazole, ceftriaxone, meropenem, tetracycline, moxifloxacin, and chloramphenicol; erythromycin and ciprofloxacin were not active. Resistance to amoxicillin and clindamycin varied. Amoxicillin susceptibility was restored by clavulanic acid.Brachyspira (previously Serpulina) pilosicoli is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 23 publications
2
30
0
Order By: Relevance
“…The therapeutic responses of patients with B. pilosicoli infections and the in vitro sensitivities of B. pilosicoli to ␤-lactam antibiotics are consistent with the identification of PBPs in this spirochete (2,3,(13)(14)(15). The demonstration of PBPs in intact B. pilosicoli cells suggests that the cell membrane is permeable to ␤-lactam antibiotics.…”
supporting
confidence: 55%
“…The therapeutic responses of patients with B. pilosicoli infections and the in vitro sensitivities of B. pilosicoli to ␤-lactam antibiotics are consistent with the identification of PBPs in this spirochete (2,3,(13)(14)(15). The demonstration of PBPs in intact B. pilosicoli cells suggests that the cell membrane is permeable to ␤-lactam antibiotics.…”
supporting
confidence: 55%
“…b-Lactam antibiotics are among the most widely used antibiotics in both humans and livestock. Decreased susceptibility to b-lactam antibiotics has been reported in Brachyspira isolates from pigs (Dassanayake et al, 2005;Mortimer-Jones et al, 2008), humans (Tompkins et al, 1987;Brooke et al, 2003;Dassanayake et al, 2005;Meziane-Cherif et al, 2008;Mortimer-Jones et al, 2008), and chickens (Hampson et al, 2006b). Except for the early paper by Tompkins et al (1987), in which isolates were not identified to species level, all the isolates displaying decreased susceptibility to b-lactam antibiotics were identified as B. pilosicoli.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, certain human and porcine isolates of B. pilosicoli have been shown to be resistant to amoxicillin (Brooke et al ., 2003). In that study resistance was associated with beta-lactamase enzyme activity, and it was suggested that this could have been acquired by horizontal transfer of beta-lactamase genes from other Brachyspira strains or bacterial species.…”
Section: Discussionmentioning
confidence: 99%